2022
DOI: 10.1039/d2an00083k
|View full text |Cite
|
Sign up to set email alerts
|

A microscopic survey on microplastics in beverages: the case of beer, mineral water and tea

Abstract: It has been reported that microplastics exist ubiquitously in aquatic and terrestrial environments. Microplastic survey on diverse daily foods with high consumption possibly containing microplastics have essential implications in clarifying...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(26 citation statements)
references
References 30 publications
(38 reference statements)
0
19
0
Order By: Relevance
“…Scientific evidence has uncovered that the plastic debris of various compositions, including polystyrene, polypropylene, and polyethylene, 3,4 exist ubiquitously in diverse environmental matrices, exerting negative impacts on wild organisms, including plants, 5 microalgae, 6 molluscs, 7 fishes, 8 and other food organisms. 9 Recent findings further suggest the occurrence of microplastic contamination in most human foods and drinks, 10 and an average microplastic intake rate in humans of 883 items per capita per day (up to 0.71 g per capita per day in another report). 11,12 Warnings have further advised that people enjoying take-out foods may suffer from exposure to microplastics at a level of up to 3.8 mg mL −1 , owing to the routine use of plastic containers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scientific evidence has uncovered that the plastic debris of various compositions, including polystyrene, polypropylene, and polyethylene, 3,4 exist ubiquitously in diverse environmental matrices, exerting negative impacts on wild organisms, including plants, 5 microalgae, 6 molluscs, 7 fishes, 8 and other food organisms. 9 Recent findings further suggest the occurrence of microplastic contamination in most human foods and drinks, 10 and an average microplastic intake rate in humans of 883 items per capita per day (up to 0.71 g per capita per day in another report). 11,12 Warnings have further advised that people enjoying take-out foods may suffer from exposure to microplastics at a level of up to 3.8 mg mL −1 , owing to the routine use of plastic containers.…”
Section: Introductionmentioning
confidence: 99%
“…The combined exposure to microplastics and antibiotics by human beings is made possible through drinking water from aquatic environments and through ingestion in the food chains. 10 exposure of microplastics and antibiotics is indeed harmful to human health, and if so, how they exert their adverse effects. In this work, we investigated the potential risk of microplastics-contaminated antibiotics to human health using a mouse model as the model mammal for human physiology.…”
Section: Introductionmentioning
confidence: 99%
“…The released microplastics can enter the human body through ingestion, inhalation, contact, and other means, posing a threat to human health. A growing number of researchers are focusing on the ingestion of microplastics by detecting the presence of microplastics in various foods, such as table salt, milk, bottled water, tea, beer, and seafood . The unintentional ingestion of microplastics has also been confirmed by the detection of various microplastics in human stool .…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] First studies on the release of particles from plastic containers found microplastics in drinking water and showed that polypropylene baby bottles release a considerable amount of micro-and nanoplastics upon use. [6][7][8][9][10][11] Currently the true extent of contamination with plastic particles in the environment and in consumer products, is not captured. Whereas the occurrence of microplastics is at the focus of many studies, knowledge on the occurrence of nanoplastics is still limited.…”
Section: Introductionmentioning
confidence: 99%